Depression and adipose essential polyunsaturated fatty acids - Mamalakis, G.; Tornaritis, M.; Kafatos, A. (Prostaglandins, leukotrienes and essential fatty acids, 2002)
The objective of the present study was to investigate the relation between adipose tissue polyunsaturated fatty acids, an index of long-term or habitual fatty acid dietary intake, and depression. The sample consisted of 247 healthy adults (146 males, 101 females) from the island of Crete. The number of subjects with complete data on all variables studied was 139. Subjects were examined at the Preventive Medicine and Nutrition Clinic of the University of Crete. Depression was assessed through the use of the Zung Self-rating Depression Scale. Mildly depressed subjects had significantly reduced (−34.6%) adipose tissue docosahexaenoic acid (DHA) levels than non-depressed subjects. Multiple linear regression analysis indicated that depression related negatively to adipose tissue DHA levels. In line with the findings of other studies, the observed negative relation between adipose tissue DHA and depression, in the present study, appears to indicate increasing long-term dietary DHA intakes with decreasing depression. This is the first literature report of a relation between adipose tissue DHA and depression. Depression has been reported to be associated with increased cytokine production, such as IL-1, IL-2, IL-6, INF-γ and INF-α. On the other hand, fish oil and omega-3 fatty acids have been reported to inhibit cytokine synthesis. The observed negative relation between adipose DHA and depression, therefore, may stem from the inhibiting effect of DHA on cytokine synthesis.